Social Adaptation and Society Perception in the Life of Widows - Abdul Malik Iskandar (Hasanuddin Journal of Sociology (HJS), 2023)
This research aims to reveal social adaptation and community perceptions of the lives of young widows in Lembang Mokallang Village, Bambang District, Mamasa Regency. This type of research is qualitative with a descriptive approach. The research location is Lembang Mokallang Village, Bambang District, Mamasa Regency. The main informants were 5 widows, 4 assistant informants from the community and 1 village or government head as the key informant. Data collection techniques were carried out through in-depth interviews, observation and documentation. Data analysis consists of data reduction, data presentation, drawing conclusions. Validation of data was carried out by triangulation and extension of observations. The research results show that in the adaptation process a widow experiences a shift in function and role as a single parent. In the adaptation process, each widow receives different perceptions from society, which causes each widow to have a different way of adapting. Every widow needs a different time to adapt after the stigma of being as a widow.